2021
DOI: 10.1097/dcr.0000000000002187
|View full text |Cite
|
Sign up to set email alerts
|

A Mobile Phone App Improves Patient-Physician Communication and Reduces Emergency Department Visits After Colorectal Surgery

Abstract: BACKGROUND: Emergency visits after colorectal surgery are common and require significant health care resources. However, many visits may be avoidable with alternative access to care. Mobile health technologies can facilitate patient access to health care providers. OBJECTIVE: We hypothesized that a mobile app for postdischarge monitoring with patient-provider communication ability would reduce emergency visits after elective abdominopelvic colorectal surgery. DESIGN: This is a prospective cohort study with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 19 publications
0
39
0
Order By: Relevance
“…In the control study period, there were 290 eligible colorectal resections, of which 185 were approached to participate in the mobile phone app study and 114 consented. 12 There were 73 patients within this control cohort that met the SDD study eligibility criteria (standard ERP cohort). Characteristics of these patients are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the control study period, there were 290 eligible colorectal resections, of which 185 were approached to participate in the mobile phone app study and 114 consented. 12 There were 73 patients within this control cohort that met the SDD study eligibility criteria (standard ERP cohort). Characteristics of these patients are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…In a pilot trial before the implementation of SDD colectomy, the use of this smart phone app was associated with reduced ED visits compared to historical controls. 12 Patients who were enrolled in that pilot trial also reported high satisfaction with the smart phone app and felt more secure after discharge because of the ability to easily communicate with their provider. Similarly, in the present study, most SDD patients reported that their questions and concerns were able to be remotely managed.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Based on these data, Lee and colleagues implemented an mHealth smartphone application for remote follow-up after elective colorectal resection to investigate its effect on post-discharge outcomes and its usability. In this study, use of a smartphone app for remote follow-up was associated with a significant reduction in preventable Emergency Department (ED) visits (IRR 0.34, 95%CI 0.12–0.97) and was associated with high usability and patient satisfaction [ 42 ]. This experience confirmed that patients were able to reliably convey important symptoms and concerns through the app in the post-discharge setting.…”
Section: Preliminary Results With Sdd Crs: the Us And Canadian Experi...mentioning
confidence: 99%
“…Amongst the open-ended reports of patient experiences, only four patients expressed pain issues in the first 72 h, although none requested additional analgesics. In particular, the use of a mHealth app for remote follow-up was associated with improved patient-physician communication post-discharge, which is essential for SDD [ 42 ]. Patients felt more secure after discharge because of the ability to easily communicate with their provider.…”
Section: Preliminary Results With Sdd Crs: the Us And Canadian Experi...mentioning
confidence: 99%